Use of Intrathecal and Intravenous Clonidine in A Case of Severe Tetanus with Acute Renal Failure - Alok Kumar; Raktima Anand; Anita Rahal; Sandhya Od (Indian Journal of Anaesthesia, 2009)
Tetanus is an acute often fatal disease produced by the Gram-positive, obligate anaerobic bacterium Clostridium tetani. Prolonged intensive care is required in severe tetanus, with the associated complications including nosocomial sepsis. Autonomic dysfunction in severe tetanus is difficult to manage and is a significant cause of mortality. We present here, use of clonidine in a case of severe tetanus with acute renal failure who was successfully managed.